Effect of powerful pulsed and continuous ion beams on the Al-Cu-Mg alloy structure - Gushchina N. V.; Makhin'ko F. F.; Ovchinnikov V. V.; Gusel'nikov V. I.; Remnev G. E. Gennady Efimovich (2016, 2016)
Title screen